Anomalous electrical resistivity anisotropy in clean reservoir sandstones. (November 2014) - North, Laurence J.; Best, Angus I.
ABSTRACT We report novel laboratory measurements of the full electrical resistivity tensor in reservoir analogue quartzose sandstones with clay contents less than 1.5%. We show that clean, homogeneous, visually uniform sandstone samples typically display between 15% and 25% resistivity anisotropy with minimum resistivity normal to the bedding plane. Thin‐section petrography, analysis of fabric anisotropy, and comparison to finite‐element simulations of grain pack compaction show that the observed anisotropy symmetries and magnitudes can be explained by syn‐depositional and post‐depositional compaction processes. Our findings suggest that: electrical resistivity anisotropy is likely to be present in most clastic rocks as a consequence of ballistic deposition and compaction; compaction may be deduced from measurements of electrical anisotropy; and the anisotropy observed at larger scales in well logging and controlled‐source electromagnetic data, with maximum resistivity normal to bedding, is most likely the result of meso‐scale (10−1 m–101 m) periodic layering of electrically dissimilar lithologies.